Money in a Developing Economy: A Case Study of Pakistan, 1953-1961 - Snyder, Wayne W. (The Review of Economics and Statistics, 1964)
HE quantity of money in economic modT els traditionally has been assumed (by Keynes, as well as others) to be an exogenously determined variable controlled uniquely by the monetary authorities. Traditional theory argues that, in a fractional reserve system, money supply is a constant multiple of the reserve bank's monetary liabilities which are controlled via the conventional instruments open market operations, changes in the required reserves ratio, and variations in the discount rate.' A current survey of monetary theory and policy states that the theory of money supply is virtually an unexplored area of monetary research.2 The contemporary theoretical and empirical controversies arising around the role of financial intermediaries reflect an awakening interest in money; and several recently completed studies of the money supply in developed economies provide further proof of this new interest.3 This study is intended to further knowledge of the process by which the supply of money is determined, but unlike previous studies it concerns money in a developing economy.